On Venezuelan pholcid spiders (Araneae, Pholcidae) - Huber, Bernhard A.; Villarreal, Osvaldo (European Journal of Taxonomy, 2020)
We present a comprehensive revision of the pholcid spider collection of M.A. González-Sponga, who between 1998 and 2011 described 22 new genera and 51 new species of Pholcidae from Venezuela. In addition, we treat the pholcid material collected during three expeditions to Venezuela conducted between 2002 and 2020. Of González-Sponga’s pholcid taxa we recognize three genera and 24 species as valid. We describe 43 new species (all from males and females) in one new and 13 previously described genera; four genera are newly recorded for Venezuela. We describe the previously unknown females of 15 species, present new records for 46 previously described species, synonymize one genus and one species, and correct numerous minor errors in previous publications on Venezuelan pholcids. At the generic level, the Venezuelan pholcid fauna now appears fairly well known, but available data on distribution and endemism suggest that many species remain undiscovered and undescribed. Despite the obvious gaps, our data are congruent with previous studies on other taxa that have the highest levels of endemism in the Venezuelan Andes, the Coastal Ranges, and the Guyana Highlands. The Falcón Region in particular shows a complex mosaic of biogeographic relationships with other regions. We provide new biological data on numerous species. We document the first cases of evolutionary microhabitat shifts in the genera Mecolaesthus Simon, 1893 and Priscula Simon, 1893. We document several cases of close congeners sharing localities, usually in slightly to conspicuously different microhabitats, sometimes apparently in identical microhabitats. We document several cases of color polymorphism, mostly intersexual, in Metagonia conica (Simon, 1893) both intersexual and among males. We document further cases of two rare phenomena in Pholcidae: use of specific non-silken structures for retreats (in Pisaboa Huber, 2000) and egg parasitism (in Priscula).